Capsular polysaccharide from Mycoplasma mycoides subsp.mycoides shows potential for protection against Contagious Bovine Pleuropneumonia - Mwirigi, M.; Nkando, I.; Olum, M.; Attah-Poku, S.; Ochanda, H.; Berberov, E.; Potter, A.; Gerdts, V.; Pérez Casal, J.; Wesonga, H.O.; Soi, R.; Naessens, Jan (Elsevier, 2016)
Contagious Bovine Pleuropneumonia (CBPP) is a severe respiratory disease caused byMycoplasma mycoides subsp. mycoides (Mmm) which is widespread in Africa. The capsule polysaccharide (CPS) of Mmm is one of the few identified virulence determinants. In a previous study, immunization of mice against CPS generated antibodies, but they were not able to prevent multiplication of Mmm in this model animal. However, mice cannot be considered as a suitable animal model, as Mmm does not induce pathology in this species. Our aim was to induce antibody responses to CPS in cattle, and challenge them when they had specific CPS antibody titres similar or higher than those from cattle vaccinated with the live vaccine. The CPS was linked to the carrier protein ovalbumin via a carbodiimide-mediated condensation with 1-ethyl-3(3-imethylaminopropyl) carbodiimide (EDC). Ten animals were immunized twice and challenged three weeks after the booster inoculation, and compared to a group of challenged non-immunized cattle. When administered subcutaneously to adult cattle, the vaccine elicited CPS-specific antibody responses with the same or a higher titre than animals vaccinated with the live vaccine. Pathology in the group of immunized animals was significantly reduced (57%) after challenge with Mmm strain Afadé compared to the non-immunized group, a figure in the range of the protection provided by the live vaccine.